Peningkatan Hasil Belajar IPAS Menggunakan Model Problem Based Learning di Kelas V SDN 12 Bukit Cangang, Kota Bukittinggi - Huda, Gilang Ramzil; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
The low learning achievement of IPAS students in the Independent Curriculum is the basis of this research. The purpose of this study is to describe how the Problem Based Learning (PBL) paradigm is used in the teaching and learning process to improve social studies learning outcomes in elementary schools. Classroom action research (PTK) is a type of research that combines quantitative and qualitative methods. There are 23 grade V elementary school students who are the subjects of this study. The researcher is a practitioner, and the teacher of class V is an observer. Two cycles of planning, implementation, observation, and reflection consist of this study project. The research findings in the first cycle teaching module resulted in an average of 84% good qualifications and 97% very good qualifications in the second cycle. The results of the learning process from teachers and students show that, on average, 82% of them have good qualifications in the first cycle, and 93% of them have very good qualifications in the second cycle. In addition, in the learning outcomes of the first cycle, an average of 81% of participants had strong qualifications, while in the second cycle, 91% of participants had very good qualifications.